Portaria 4CCR nº 16, de 10 de novembro de 2020 - Carlos Frederico Santos; Eliana Peres Torelly de Carvalho|Juliano Baiocchi Villa-Verde de Carvalho; Carlos Alberto Carvalho de Vilhena Coelho (DMPF-e, Brasília, DF, 16 nov. 2020. Caderno Extrajudicial, p. 8., 2020)
Altera a composição do Grupo de Trabalho Intercameral - Agroecologia.